Control of growth by picolinic acid: Differential response of normal and transformed cells - Fernandez-Pol, J. A. (1977)
Picolinic acid reversibly inhibits the growth of cultured cells. Fourteen other pyridine derivatives were ineffective or toxic. Untransformed normal rat kidney (NRK) cells are reversibly arrested in the G(1) stage of the growth cycle as shown by cell counts, mitotic index, [(3)H]thymidine incorporation, and flow microfluorometry. Flow microfluorometry was used to monitor the effects of picolinic acid on numerous other cell lines. Normal cells are blocked in G(1), whereas transformed cells show responses that are dependent upon the transforming virus and independent of species or origin of the cell line. Kirsten sarcoma virus-transformed cells are blocked in G(1). Simian virus 40-transformed cells progress to a G(2) block. Cells transformed by polyoma or Harvey sarcoma virus with Moloney virus coat have flow microfluorometry profiles that indicate blocks in both G(1) and G(2). Cells transformed with Moloney sarcoma virus are not blocked in a specific phase of the cell cycle. Picolinic acid does not change the levels of NAD(+) plus NADH; however, the growth inhibition by picolinic acid is partially overcome by nicotinamide. These results suggest that picolinic acid interacts with a specific growth control mechanism that may involve NAD(+) and that this control mechanism is altered by different transforming viruses in different manners.